Instilling Islamic Values in Early Childhood through the Story of Prophet Yusuf: A Literature Review - Futhira, Nadia; Sutrisno, Sutrisno; Junianti, Fitri (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Background of the study: Instilling Islamic values in early childhood lays a strong foundation for building moral character and spiritual awareness. Early childhood is a critical stage when children are highly responsive to the values and behaviors around them. In Islamic education, storytelling especially stories of the Prophets has long been seen as an effective way to teach values. One powerful example is the story of Prophet Yusuf, which contains many important lessons relevant to character education. Aims and scope of paper: This paper explores how Islamic values can be introduced to young children through the story of Prophet Yusuf. It focuses on key values found in the narrative, such as honesty, patience, piety, forgiveness, and gratitude. The paper also discusses how these values can be taught using methods that are suitable for the developmental stage of early learners. These methods include storytelling, discussion, roleplay, and daily routines that reinforce good behavior. Methods: The study uses a qualitative library research method. Data were collected from secondary sources, including academic books, journal articles, and interpretations of the Qur’an that examine Prophet Yusuf’s story and Islamic character education. The analysis follows a descriptive-interpretive approach to identify key themes and teaching strategies. Results: The findings show that Prophet Yusuf’s story is rich in Islamic values and can be a valuable tool for moral teaching in early childhood. The values in the story are relatable and can help children develop positive behavior when taught in a simple and engaging way. Contribution: This paper contributes to Islamic early childhood education by offering a structured approach to using religious stories for value-based learning. It also shows that Qur’anic stories are not only spiritually meaningful but also culturally relevant for building character. The study encourages educators and parents to use storytelling as a practical and meaningful method to support children’s moral and spiritual growth